Arrhythmogenic right ventricular cardiomyopathy - What Is New since 2023 European Society of Cardiology Guidelines? Current Knowledge, Literature Review - Magdalena Balwierz (Quality in Sport)
Introduction: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically conditioned disease, characterized by gradual fibro-fatty replacement of myocardium and tendency to ventricular arrhythmias and heart failure. ARVC is included in a group of inherited similar clinical entities characterized by similar remodeling changes, named in general arrhythmogenic cardiomyopathies (ACM). The new guidelines of European Society of Cardiology (ESC) for the management of cardiomyopathies (2023) redefine arrhythmogenic left ventricular cardiomyopathy (ALVC), left dominant ARVC, or arrhythmogenic dilated cardiomyopathy (DCM) as non-dilated left ventricular cardiomyopathy (NDLVC). The diagnostic process is based on Padua Criteria (2020) according to ESC guidelines and includes: right ventricle dysfunction evidence, endomyocardial biopsy results, defects of repolarization and conduction, arrhythmias and family history. However, in 2024 European Task Force consensus with modified guidelines was proposed. The treatment focuses on arrhythmias and heart failure management, prevention of sudden cardia death and family screening. Multidisciplinary approach is required to the proper management of the patients.